Cos²x\2- sin²x\2=sin(π\2-2x) cos²x\2=(1+cosx)\2 sin²x\2=(1-cos)\2 sin(π\2-2x)=cos2x
(1+cosx)\2-(1-cosx)\2=cos2x cos2x=2cos²x-1
1+cosx-1+cosx=2(2cos²x-1)
4cos²x-2cosx-2=0
2cos²x-cosx-1=0 введём замену переменной . Пусть cosx=y
2у²-у-1=0
D=1-4·2·(-1)=9 √D=3
y1=(1+3)\4=1
y2=(1-3)\4=-1\2
Вернёмся к замене : cosx=y1
cosx=1
x=+- arccos1+2πn n∈Z
x=2πn n∈Z
cosx=y2
cosx=-1\2
x=+- arccos(-1\2)+2πm m∈Z
так как значение арккосинуса отрицательное , то arccos(-1\2)=π-π\3=2π\3
x=+-2π\3+2πm m∈Z
1) 2,02 2) 4,441 3) 12,963 4) 31,2 5) 4,143 6) 10,1
Пошаговое объяснение:
1) х+25,3=27,32
х=27,32-25,3
х=2,02
2) 7,79+х=12,231
х=12,231-7,79
х=4,441
3) 48,7-х=35,737
х= 48,7-35,737
х= 12,963
4) 15,6+х=15,6
х=15,6+15,6
х=31,2
5)х-3,713=0,43
х=3.713+0,43
х=4,143
6)х-2,2=7,9
х=7,9+2,2
х=10,1